Copper-Catalyzed Cross-Coupling of O-Alkyl Hydroxamates with Aryl Iodides - Kukosha, Tatyana; Trufilkina, Nadezhda; Belyakov, Sergey; Katkevics, Martins (Synthesis, 2012)
N-Aryl-O-alkylhydroxamic acid derivatives were prepared by copper-catalyzed cross-coupling of hydroxamates with aryl iodides. The reaction conditions are compatible with standard hydroxy-protecting groups on the hydroxylamine moiety and are applicable to a broad range of coupling partners.
Keywords: copper; arylation; cross-coupling; amides; halides; catalysis